Origins and evolution of innate lymphoid cells: Wardens of barrier immunity. (22nd May 2017) - Neill, D. R.; Flynn, R. J.
Summary: The identification, in the late 2000s, of innate lymphoid cells (ILCs) as a new class of non‐B, non‐T lymphocytes has led to global efforts to understand their functions, plasticity and evolutionary origins and to define their place within the leucocyte family. Although this work has uncovered striking similarities in the developmental cues, lineage‐specific transcription factors and functional capacities of innate and adaptive lymphocytes, it has become clear that ILCs play a unique and defining role as stewards of barrier defence and that this sets them apart from their adaptive cousins. This review will explore how the dynamic environment of barrier surfaces has shaped ILC evolution and functionality. We highlight the critical importance of the microbiome and the unique role of ILCs as environmental sensors. We reflect on how these factors may have influenced the development of ILC2s and barrier immunity in the context of exposure to helminth parasites that have been driving forces of our evolution throughout human history. Finally, we argue that the plasticity of ILC function reflects their role as first responders to environmental change.